Maternal autoimmune thyroid disease and pregnancy complication - Gudović Aleksandra; Spremović-Radjenović Svetlana; Lazović Gordana; Marinković Jelena; Glišić Andreja; Milićević Srboljub (Vojnosanitetski Pregled)
Background/Aim. Thyroid disorders exert a great impact on pregnancy course and outcome. The aim of the study was to investigate impact of autoimmune thyroid disorders on pregnancy course and outcome, frequency of pregnancy complications and pregnancy loss. Methods. We followed 63 pregnancies prospectively during the period 1985-2007, 28 with hyperthyroid and 15 with hypothyroid autoimmune disorders, and 20 healthy pregnancies. Follow up included clinical, sonographic and laboratory investigations, including OGTT and postprandial glicemia. Results. There was no difference between previous preterm and term labor in the observed groups (χ² = 2.309; p > 0.05). Analysis of previous early pregnancy loss showed no significance (χ² = 4.918; p > 0.05), including varieties of spontaneous and missed abortion (Fisher, p < 0.05). The hypothyroid patiens developed gestational diabetes more frequently than the controls (χ² = 7.638; p = 0.022), which is not the case with hyperthyroid patients (χ² = 1.078; p > 0.05), or between the groups with thyroid disorders (χ² = 3.619; p > 0.05). There was no difference among the groups in developing pregnancyinduced hypertension (χ ² = 1.953; p > 0.05). Conclusions. Controlling thyroid diseases reduces pregnancy complications. Development of gestational diabetes in hypothyroid patients requires controlling glycoregulation in all pregnant women with hypothyroidism.